INFLUENCE OF SELF-ESTEEM AND OBJECTIVE KNOWLEDGE FINANCIAL OF THE FINANCIAL BEHAVIOR IN YOUNG ADULTS WITH SUBJECTIVE FINANCIAL KNOWLEDGE MEDIATION AS VARIABLE - Rex Gosal; Dewi Astuti; Evelyn Evelyn (International Journal of Financial and Investment Studies (IJFIS), 2021)
This study aims to determine the effect of self-esteem and objective financial knowledge on financial behavior. In addition, this study also seeks to assess the impact of subjective financial knowledge as a mediating variable between self-esteem and objective financial knowledge on financial behavior. The population of this research is young adults in Surabaya. The research sample is the population aged 25-34 years and invested in stocks for less than three years. Data analysis method used is partial least square analysis. The results showed that self-esteem had a significant effect on financial behavior, objective financial knowledge had no considerable impact on financial behavior, subjective financial knowledge had a significant effect on financial behavior, self-esteem, and financial. In addition, objective knowledge has a significant effect on subjective financial knowledge, and self-esteem and financial knowledge objective have a significant impact on financial behavior with financial knowledge subjective as a mediating variable.